Consent and research governance in biobanks: evidence from focus groups with medical researchers. - Whitley, E; Kanellopoulou, N; Kaye, J (2012)
Much is known about patient attitudes to ethical and legal questions in the context of biobanking, particularly regarding privacy protection and consent. However, little is known about the attitudes of medical researchers who use biobanks for research to these issues. Four focus groups with medical researchers in the UK were conducted in 2010-2011. The study highlights a range of issues associated with the research oversight and consent process (including obtaining ethical approval to use biobank samples and particular concerns for international studies), the benefits and limitations of broad consent and the possibilities of revoking consent. Many of these issues originate in the relatively static consent processes that currently govern the biobanking process. However, it is now possible to develop reliable, dynamic processes using information technology that can resolve many of these ethical and legal concerns. The 'dynamic consent' approach therefore offers the opportunity to fundamentally transform the process of medical research in a manner that addresses the concerns of both patients and medical researchers.